Collagen gel protects L929 cells from TNFα-induced death by activating NF-κB. (3rd September 2017) - Wang, Hong-Ju; Li, Meng-Qi; Liu, Wei-Wei; Hayashi, Toshihiko; Fujisaki, Hitomi; Hattori, Shunji; Tashiro, Shin-ichi; Onodera, Satoshi; Ikejima, Takashi
ABSTRACT: Purpose: Type I collagen is one of the most abundant components of extracellular matrix. We previously illustrated that murine fibrosarcoma L929 cells grew well on type I collagen gel and escaped from TNFα-induced cell death. In this study, we investigated the mechanism underlying the protective effect of collagen gel. Material and methods: We used western blot, confocal microscopy, MTT assay and flow cytometry by introducing fluorescence staining to determine the expression levels of nuclear factor kappa B (NF-κB), inhibitory ratio and autophagy. Results: L929 cells on collagen gel showed higher expression of NF-κB in the nucleus. Inhibition of NF-κB with pyrrolidine dithiocarbamate hydrochloride (PDTC) or knockdown by NF-κB-siRNA canceled the protective effect of collagen gel on L929 cells from TNFα-induced death, suggesting for the role of NF-κB in the protection from cell death. We found a new aspect of the effect of PDTC on L929 cells cultured on collagen gel. PDTC alone without TNFα induced apoptosis in the L929 cells cultured on collagen gel but not the cells on plastic dish. The apoptosis induction of the L929 cells cultured on collagen gel with PDTC was repressed by inhibiting autophagy with chloroquine, an autophagy inhibitor, suggesting that autophagy contributes to the death induced by the treatment with PDTC. Possible underlying mechanism of this finding is discussed. Conclusion: NF-κB played an important role in protecting the L929 cells cultured on collagen gel from TNFα-induced death.